The nitrosated bile acid DNA lesion O(6)-carboxymethylguanine is a substrate for the human DNA repair protein O(6)-methylguanine-DNA methyltransferase - Senthong, Pattama (Oxford University Press, 2013)
The consumption of red meat is a risk factor in human colorectal cancer (CRC). One hypothesis is that red meat facilitates the nitrosation of bile acid conjugates and amino acids, which rapidly convert to DNA-damaging carcinogens. Indeed, the toxic and mutagenic DNA adduct O(6)-carboxymethylguanine (O(6)-CMG) is frequently present in human DNA, increases in abundance in people with high levels of dietary red meat and may therefore be a causative factor in CRC. Previous reports suggested that O(6)-CMG is not a substrate for the human version of the DNA damage reversal protein O(6)-methylguanine-DNA methyltransferase (MGMT), which protects against the genotoxic effects of other O(6)-alkylguanine lesions by removing alkyl groups from the O(6)-position. We now show that synthetic oligodeoxyribonucleotides containing the known MGMT substrate O(6)-methylguanine (O(6)-MeG) or O(6)-CMG effectively inactivate MGMT in vitro (IC(50) 0.93 and 1.8 nM, respectively). Inactivation involves the removal of the O(6)-alkyl group and its transfer to the active-site cysteine residue of MGMT. O(6)-CMG is therefore an MGMT substrate, and hence MGMT is likely to be a protective factor in CRC under conditions where O(6)-CMG is a potential causative agent.